Pomoc publiczna na szkolenia pracowników a konkurencyjność gospodarki Unii Europejskiej - Podsiadło, Piotr (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The paper discusses guidelines for implementation of art. 107-109 of the Treaty on the Functioning of the European Union, from the point of view of state aid for training. Training usually generates positive externalities for society as a whole, since it increases the pool of skilled workers from which other firms may draw, improves the competitiveness of the EU industry and plays an important role in the EU employment strategy. Statistical analysis was carried out on state aid granted by the EU Member States in the period 2001-2014 - from the perspective of its impact on competitiveness of these countries. This should lead to verification of thesis that the amount of state aid granted by the EU Member States for training, should positively correlate with the size of the GDP per capita of these countries